2001
DOI: 10.1080/gye.15.2.123.128
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the genetic polymorphism in the region ofCYP17gene encoding 5′-UTR in patients with polycystic ovarian syndrome

Abstract: Polycystic ovarian syndrome (PCOS) is a prevalent endocrine disorder, which is the most common cause of anovulatory infertility and hirsutism. It is caused by an overproduction of androgens in theca cells. In the ovary, androgen synthesis is regulated by 17 alpha-hydroxylase/17,20-lyase enzyme complex containing P450c17 (CYP17). In some individuals, the promoter region of CYP17 gene contains a T-->C substitution that creates an Sp1 site at position-34. This polymorphism generates a recognition site for the Msp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 12 publications
(12 reference statements)
0
4
0
1
Order By: Relevance
“…In Chinese women, a polymorphism in the promoter region of the aldosterone synthetase gene ( CYP11B2 ), which affects the balance of the ovarian renin–angiotensin system, has been linked to PCOS susceptibility (Zhao et al ., 2003). A polymorphism in the gene for 17α-hydroxylase ( CYP17A1) , which is active in estrogen biosynthesis, was not associated with PCOS susceptibility (Techatraisak et al ., 1997; Diamanti-Kandarakis et al ., 1999; Marszalek et al ., 2001). The CYP19A1 gene encodes a key component of aromatase, which catalyses the production of estrogens from androgens.…”
Section: Resultsmentioning
confidence: 99%
“…In Chinese women, a polymorphism in the promoter region of the aldosterone synthetase gene ( CYP11B2 ), which affects the balance of the ovarian renin–angiotensin system, has been linked to PCOS susceptibility (Zhao et al ., 2003). A polymorphism in the gene for 17α-hydroxylase ( CYP17A1) , which is active in estrogen biosynthesis, was not associated with PCOS susceptibility (Techatraisak et al ., 1997; Diamanti-Kandarakis et al ., 1999; Marszalek et al ., 2001). The CYP19A1 gene encodes a key component of aromatase, which catalyses the production of estrogens from androgens.…”
Section: Resultsmentioning
confidence: 99%
“…In 1994, Carey et al showed significant association of this polymorphism with PCO and male pattern baldness in a family-based study [ 72 ]; however, these findings were not persistent when they increased the sample size [ 73 ]. On similar lines, this polymorphism was not found to be a significant factor for PCOS development in British [ 74 ], Slovenian [ 75 ], Polish [ 76 ], American [ 77 , 78 ], Korean [ 79 ], Chilean [ 80 ], Chinese [ 81 ], Thai [ 82 ], and Indian [ 83 ] women with PCOS or even in Turkish adolescents [ 84 ]. In contrast, Indian women with PCOS showed significantly increased frequency of C allele [ 53 ].…”
Section: Genetics Of Pcosmentioning
confidence: 99%
“…After screening the full text of these publications, 10 articles were excluded for not meeting the inclusion criteria. Ultimately, 19 eligible case–control studies ( 23 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ) were included in this review in Fig. 1 .…”
Section: Resultsmentioning
confidence: 99%
“…This finding is analogous with the study done by Park ( 38 ) showing higher expression in the recessive model of CYP17 genotype among PCOS compared with control subjects in a Korean population. However, null associations were observed in Caucasians by Marszalek ( 37 ), Echiburú ( 27 ) and Ushasi Banerjee ( 28 ). Consequently, whether the significant relationship existed in Caucasian women could not be assessed owing to the small number of women in this category, which remains unknown and needs further examination.…”
Section: Discussionmentioning
confidence: 97%